P.031 Intravenous immunoglobulins (IVIG) therapy in chronic inflammatory demyelinating polyneuropathy (CIDP): time to maximal recovery. (June 2019) - Opala, A; Baker, S
Abstract : Background: The response of Chronic Inflammatory Demyelinating Polyneuropathy (CIDP) to Intravenous Immunoglobulins (IVIG) treatment is well established . However, determination if patients not responding to 2 IVIG treatments or those whose condition stabilizes (ICE Trial) may benefit from additional doses remains unclear. We aim to identify time period required to reach maximal strength gains from IVIG treatment. Methods: Retrospective chart review of 14 patients with CIDP was performed. Change in Grip strength (GS), Knee extension (KE), Elbow Flexion (EF) and Dorsflexion(DF) was analyzed with a dynamometer during IVIG therapy. Averages for : percent change from baseline(Max%Δ), cumulative grams(g) of IVIG and time in weeks(w) required for maximal strength recovery was determined per function (+/−SEM).Anciliary therapy for all patients was recorded. Results: Strongest improvement was observed for DF(124+/−30%, p<0.001), followed by KE(113+/−19%, p<0.01), GS(100+/−21%, p<0.001) and EF(98+/−14%p<0.05).GS improved the fastest(19.1+/−3w) followed by DF(29.5+/−7w), KE(29.6+/−4w) and EF(31+/−6w). Cumulative IVIG dose to reach Max%Δ was highest for EF(869+/−201g) and lowest for GS(573+/−78g). Conclusions: Our study has demonstrated effectiveness of multiple treatments with IVIG to reach significant improvement in strength. Different muscle groups manifested different time-dependency, reflecting variable amounts of IVIG required. Improvement was identified to be present on a ongoing basis, with therapy lasting between 19.1-31 weeks, requiring between 869-573g of IVIG.